Peningkatan Sikap Ilmiah Melalui Penerapan Model Pembelajaran Penemuan (Discovery Learning) - Raudatus Solihah (Journal of Classroom Action Research, 2023)
This research is a classroom action research that aims to improve the scientific attitude of class XI MIA-1 students in the subject of Chemical Equilibrium in the 2022/2023 academic year. PTK is carried out through 2 cycles. The data collected in this study consisted of qualitative data. Qualitative data were obtained from observing the implementation of learning and students' scientific attitudes in learning, the data were classified based on the aspects that were used as the focus of analysis. This qualitative data is then associated as a basis for describing the successful application of the discovery learning model (Discovery Learning) which is characterized by an increase in students' scientific attitudes in learning chemistry on Chemical Equilibrium material. The results of the study show that the discovery learning model applied to Chemistry learning in Chemical Equilibrium material is proven to improve students' scientific attitudes, which include discipline, cooperation, honesty, confidence and responsibility. There was an increase in the percentage of scientific attitudes in all aspects. For the aspect of discipline, there was a significant increase from 72% to 80%. So that learning Chemistry with the discovery learning model is proven to be able to improve students' scientific attitudes